2015
DOI: 10.1371/journal.pone.0123640
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Genes Encoding Calcineurin B-Like Protein Family in Legumes and Their Expression Analyses in Chickpea (Cicer arietinum L.)

Abstract: Calcium ion (Ca2+) is a ubiquitous second messenger that transmits various internal and external signals including stresses and, therefore, is important for plants’ response process. Calcineurin B-like proteins (CBLs) are one of the plant calcium sensors, which sense and convey the changes in cytosolic Ca2+-concentration for response process. A search in four leguminous plant (soybean, Medicago truncatula, common bean and chickpea) genomes identified 9 to 15 genes in each species that encode CBL proteins. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…As a second messenger in plants, calcium signals response to various external and internal stimuli, and regulate stomatal opening, root hair elongation and pollen tube growth [37][38][39]. In the calcium signaling pathway, calmodulin-like proteins (CaMs), calcium-dependent protein kinases (CDPKs) and Calcineurin B-like proteins (CBLs), were three main classes of elongation factor (EF)-hand Ca 2+ sensors [40,41], and it has reported that the ZmCBL9 and calcineurin B-like-interacting protein kinases (ZmCIPKs) interact with each other to regulate the ABA responses in maize [42].…”
Section: Discussionmentioning
confidence: 99%
“…As a second messenger in plants, calcium signals response to various external and internal stimuli, and regulate stomatal opening, root hair elongation and pollen tube growth [37][38][39]. In the calcium signaling pathway, calmodulin-like proteins (CaMs), calcium-dependent protein kinases (CDPKs) and Calcineurin B-like proteins (CBLs), were three main classes of elongation factor (EF)-hand Ca 2+ sensors [40,41], and it has reported that the ZmCBL9 and calcineurin B-like-interacting protein kinases (ZmCIPKs) interact with each other to regulate the ABA responses in maize [42].…”
Section: Discussionmentioning
confidence: 99%
“…MPK genes were reported to participate in response to cold, drought, ultraviolet light, oxidation stress and disease in many crops [4547]. Thirdly, CBL7 , as one of the plant calcium sensors, can interact with CIPKs to form CBL-CIPK complexes that mediate responses to salinity, drought stress, phosphorous deficiency and ABA signaling [4850]. Li et al [49] indicated that over-expression of soybean CBL1 enhances tolerance to salinity and drought stress in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…First strand cDNA was synthesized by High Fidelity cDNA synthesis kit (Roche Diagnostics GmbH, Germany) and oligo dT primer at 50°C for 30 min. Quantitative real-time PCR (qRT-PCR) experiments and calculations were performed using three technical and three biological replicates following the methods described before (Meena et al, 2015 ). Briefly, the reaction was performed in 10 μl reaction volume with 225 nM of each of the forward and reverse primers (Supplementary Table 2 ) and 2X Power SYBR Green PCR master mix (Applied Biosystems, CA, USA) using Vii A 7 Real-Time PCR System (Applied Biosystems, CA, USA).…”
Section: Methodsmentioning
confidence: 99%